Islamic wealth management: is the nominee a trustee or beneficiary? An analysis on the application of the nomination instrument in the disposition of property in Malaysia from the perspective of Islamic law - Abdullah, Mohamad Asmadi (Sweet & Maxwell Asia, 2011)
Nomination is originally a means to expedite the process of the administration of a deceased Muslim’s estate. With nomination, a nominee therefore has a legal right to claim the property of the deceased from the relevant financial institution such as Insurance companies, Takaful companies, Tabung Haji and Employee Provident Fund. However, there is a question pertaining to the status of the nominee whether he is a trustee or a beneficiary. The fatwā issued by the National Fatwa Committee suggest that a nominee acts only as a trustee. However, looking into the decisions of the civil courts as well as the Shariah court, a nominee could be a beneficiary. This research is undertaken to examine the nature of the nomination process and to identify any similarities and differences between nomination, wasiyyah and hibah according to the Islamic law in order to determine whether a nominee is a trustee or a beneficiary.